ETHNIC FEMALE COSTUME SET: ORIGINS, CONSTRUCTIVE AND COMPOSITIONAL - ОСТАПЕНКО, Н. В.; Яковлєв, М. І.; Луцкер, Т. В.; Сімак, А. І.; Амірян, А. С. (Art and Design, 2022)
Aim of the research is to investigate the characteristic artistic and compositional features of the Armenian female costume set of the late XVII century and the beginning of the ΧΧ century through a prism of traditional culture. Research methods. Visual, analytical, information and research approaches, methods of system and comparative analysis are used. The method of artistic and compositional analysis of regional female Armenian costume sets are used when considering the types of clothing, footwear, jewelry, etc. The emphasis is placed on the use of materials in Armenian, Old Languages and meaningful visual group of the source base. Obtained results include the analysis of the ethnic female costume set of Armenia "taraz" of the end of the XVII century and the beginning of the 20th century. Its assortment is generalized, products characteristic features are described by regional factors, compositional and constructive features of Armenian clothes are singled out by social, ceremonial and age differences. The ornamental decoration and embroidery with various materials in the context of rituals are emphasized. A comparative analysis of constructive and decorative features of Armenian women's underwear was conducted on social grounds. The figurative and stylistic features of female clothing set of the Yerevan region of the XIX century are revealed. The generalized structure of the ethnic women's costume of the Yerevan region of the end of the XVII century and early nineteenth century is graphically presented. On the basis of creative source, a modern festive women's set consisting of a blouse and a dress was developed and made. The scientific novelty. The female costume set of Armenia of the end of the XVII century and the beginning of the ΧΧ century is typified by assortment groups, its constituent products of the western and eastern Armenian regions are characterized, their compositional and constructive features are revealed. The constructive and decorative characteristics of lingerie of married and unmarried women of Armenia are compared. The structure of ethnic female costume of the Yerevan region of the end of the XVII century and the beginning of the nineteenth century is generalized. The practical significance s is that the compositional and constructive features of different assortment groups of the ethnic women's costume set of Armenia "taraz" of the end of the XVII century and the beginning of the ΧΧ century are described by regions. The ornamental decoration of the products in the context of rituals is presented. The figurative and stylistic features of women's clothing set of the Yerevan region of the XIX century are described. On the basis of a creative source, a modern festive women's set consisting of a blouse and a dress with the use of ethnic motifs was developed and made.